Numerical analysis of effectiveness of strengthening concrete slab in tension of the steel-concrete composite beam using pretensioned CFRP strip = Analiza numeryczna skuteczności wzmocnienia wstępnie naprężonymi taśmami CFRP rozciąganej płyty stalowo-betonowej belki zespolonej - Jankowiak, Iwona; Madaj, Arkadiusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
One of the methods to increase the load carrying capacity of the reinforced concrete (RC) structure is its strengthening by using carbon fiber (CFRP) strips. There are two methods of strengthening using CFRP strips - passive method and active method. In the passive method a strip is applied to the concrete surface without initial strains, unlike in the active method a strip is initially pretensioned before its application.
Keywords: composite beam; FE analysis; CFRP strips; strengthening of composite beam; concrete in tension; Concrete Damage Plasticity model; belka zespolona; analiza MES; taśmy CFRP; wzmacnianie belek zespolonych; beton rozciągany; beton plastyczny